THE INFLUENCE OF ACCESS TO FINANCING, FINANCIAL LITERACY AND ENTREPRENEURIAL COMPETENCE ON UMK PERFORMANCE IN KENDARI CITY - Muhammad Khafif Hamdun Syahadat; Suharno; Etriya Etriya (Jurnal Agribisnis Indonesia, 2025)
Kendari City although the growth of MSEs shows a positive trend, challenges such as access to financing, financial literacy and entrepreneurial competence still need to be overcome to encourage positive MSE performance. The existing literature still does not conclusively state how the role and how to utilize information about financial access, financial literacy, and entrepreneurial competence. Therefore, there is a high urgency to conduct research on this subject, agat obtained benefits for the development of MSEs. This study aims to analyze the effect of access to financing, financial literacy and entrepreneurial competence on the performance of MSEs in Kendari City. Data collection using survey techniques located in Kendari City. The number of samples in this study as many as 165 respondents who have a SIUP. Data were analyzed using PLS-SEM method. The results showed that access to financing, financial literacy and entrepreneurial competence have a positive effect on the performance of MSEs. Access to financing is proven to improve the performance of micro and small enterprises (SMEs). Similarly, financial literacy improves performance. Furthermore, entrepreneurial competence also improves the performance of MSEs. Policy implications and recommendations that can be followed up by simplifying credit application requirements and procedures, conducting regular financial management training and training in skills and product innovation supported by collaboration between local governments and financial institutions to encourage sustainable growth of MSEs in Kendari city.